2023
DOI: 10.14740/jocmr4848
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation Between Changes in Serum Albumin Levels and Breakfast Non-Protein Calorie/Nitrogen Ratio in Geriatric Patients

Abstract: Background: Differences in nutrition intake by meal intake time of geriatric patients may affect albumin (Alb) synthesis ability. Methods:We included 36 geriatric patients (81.7 ± 7.7 years; 20 males and 16 females) as subjects. We calculated their dietary patterns (DPs) by computing intake by breakfast, lunch, and dinner, as well as by nutrient, for a weight of 1 kg/day for 4 weeks after hospitalization. We confirmed the relationship between "DP with a positive correlation with breakfast protein" and the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…We also found that the NPC/N ratio in elderly patients’ nutritional intake may influence their discharge locations [ 5 ]. Additionally, we have demonstrated that to improve Alb levels at discharge, it might be useful to increase the proportion of carbohydrates within the permitted range in the NPC/N ratio of breakfast and improve non-protein energy intake obtained from breakfast [ 6 ]. Therefore, the NPC/N ratio can be applied to evaluate the nutrient composition of meals in this study.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the NPC/N ratio in elderly patients’ nutritional intake may influence their discharge locations [ 5 ]. Additionally, we have demonstrated that to improve Alb levels at discharge, it might be useful to increase the proportion of carbohydrates within the permitted range in the NPC/N ratio of breakfast and improve non-protein energy intake obtained from breakfast [ 6 ]. Therefore, the NPC/N ratio can be applied to evaluate the nutrient composition of meals in this study.…”
Section: Introductionmentioning
confidence: 99%